Manufacturing method of low-formaldehyde scratch-resistant veneer impregnated paper
By adopting the manufacturing method of low-aldehyde scratch-resistant veneer impregnated paper, a mixture of homemade ultra-low molar ratio urea formaldehyde resin and wear-resistant slurry is used to solve the problems of high formaldehyde emission and poor scratch-resistant performance of traditional veneer impregnated paper, achieving environmentally friendly, durable, beautiful and easy-to-maintenance effects.
Patent Information
- Application Number
- CN202510028357.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional decorative panel impregnated paper has the problems of high formaldehyde emission, high brittleness, easy to break, and poor scratch resistance, which is difficult to meet the needs of modern people for environmental protection, durability and aesthetics.
The manufacturing method of low-aldehyde scratch-resistant veneer panel impregnated paper is adopted. By making ultra-low molar ratio urea formaldehyde resin and adding a mixture of melamine formaldehyde resin and wear-resistant slurry to the coating area, it is dried and processed many times to improve its wear resistance, scratch resistance and moisture resistance.
It effectively reduces the indoor formaldehyde content, improves the surface wear resistance and scratch resistance, maintains good moisture resistance, meets different decoration styles and personal preferences, and reduces the maintenance cost for long-term use.
Smart Images

Figure BDA0005233433130000041 
Figure BDA0005233433130000051 
Figure BDA0005233433130000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of home decoration materials, relates to impregnated paper, and in particular to a method for manufacturing low-formaldehyde scratch-resistant decorative panel impregnated paper. Background Art
[0002] Decorative panels are the main raw materials for modern home decoration and can be used in door panels, wardrobes, wall panels and other usage scenarios. Traditional decorative panel surface decoration materials include impregnated film paper, PET film, PVC film, PP film, etc. Among them, impregnated paper has the advantages of low price and wide application range, but impregnated paper generally has the disadvantages of high formaldehyde emission, high brittleness, easy breakage, and poor scratch resistance. Therefore, low-formaldehyde and scratch-resistant decorative panel impregnated paper is more competitive in the market. First of all, with the improvement of people's environmental awareness, the requirements for indoor air quality are getting higher and higher. Low-formaldehyde and scratch-resistant decorative panels can effectively reduce indoor formaldehyde content and reduce harm to the human body. They comply with the country's clear regulations on formaldehyde emission limits in artificial boards and their products, ensuring that the products are safe and harmless. Secondly, the low-formaldehyde scratch-resistant decorative panels have been specially treated, and the surface has excellent wear resistance and scratch resistance. They can withstand wear and scratches in daily use and maintain long-term beauty. At the same time, its good moisture-proof performance also enables it to maintain stable performance in a humid environment and is not easy to deform or mold. In addition, low-formaldehyde scratch-resistant veneer panels are available in a variety of colors and patterns to meet the needs of different decoration styles and personal preferences. Consumers can also customize the color, pattern and size of the veneer panels according to their needs to create a unique home environment. Finally, due to its smooth surface and good moisture resistance, low-formaldehyde scratch-resistant veneer panels are also very convenient in daily cleaning and maintenance. Stains or oil stains can be removed by simply wiping gently with a damp cloth, reducing long-term maintenance costs.
[0003] In summary, the use of low-formaldehyde scratch-resistant decorative panels can improve the quality and comfort of home decoration and meet the needs of modern people for environmental protection, durability, and beauty. Therefore, it is imperative to develop high-quality and low-cost impregnated paper suitable for decorative panels. Summary of the invention
[0004] The object of the present invention is to provide a method for manufacturing low-formaldehyde scratch-resistant decorative panel impregnated paper to solve the problems raised in the above-mentioned background technology.
[0005] Technical Solution
[0006] A method for manufacturing low-formaldehyde scratch-resistant decorative panel impregnated paper comprises the following steps:
[0007] A. The base paper of the film paper is pre-impregnated in a glue dipping tank. The base paper of the film paper is 50-150g of decorative paper. The excess glue and the air in the paper are squeezed out by a glue squeezing roller, so that the mass of the resin attached to the surface of the film paper is 50±3% of the mass of the base paper;
[0008] B. Dry in the oven once, temperature 115~135℃, wind speed 900~1100m 3 / min, speed 20~25m / min;
[0009] C. Apply a mixture of melamine formaldehyde resin and wear-resistant pulp in the coating area, the upper coating amount is 40-60% of the base paper mass, and the lower coating amount is 40-60% of the base paper mass;
[0010] D. Secondary drying in oven, temperature 110℃~140℃, wind speed 800~1000m 3 / min, speed 20~25m / min;
[0011] E. Cutting, stacking and packaging;
[0012] The glue in step A is a homemade ultra-low molar ratio urea-formaldehyde resin, in which water, a penetrant, and a curing agent are added to the resin to form an impregnation solution, wherein water accounts for 8-12% of the mass of the urea-formaldehyde resin, the penetrant accounts for 0.3-0.5% of the mass of the urea-formaldehyde resin, and the curing agent accounts for 0.2-0.4% of the mass of the urea-formaldehyde resin. The penetrant model is F14, and the curing agent model is 1448, both of which are purchased from Shanghai Hongyi International Trade Co., Ltd.;
[0013] The preparation method of the self-made ultra-low molar ratio urea-formaldehyde resin comprises:
[0014] (a) Add formaldehyde into the reaction kettle and stir, and adjust the pH value to 7.5-8.5 with caustic soda;
[0015] (b) adding urea once and heating to 70-90°C, stopping heating, slowly heating to 95-100°C by self-heating and keeping warm for 50-70 minutes;
[0016] (c) adding a small amount of formic acid to adjust the pH value to 4.6-4.8, reacting for 20-25 minutes and measuring the fog point in 20°C water;
[0017] (d) adding melamine, adjusting the pH to 7.3-7.7 with a small amount of ethanolamine solution, adding secondary urea after keeping the temperature for 10-15 minutes, and then continuing to keep the temperature and add water for 20-40 minutes;
[0018] (e) Cool down to 60-70°C, add urea three times, continue to cool down to 40°C or below, and produce glue.
[0019] According to a preferred embodiment of the present invention, in step (a), the formaldehyde accounts for 40-60% of the total mass of the urea-formaldehyde resin, and the caustic soda is sodium hydroxide with a mass percentage concentration of 30-40%.
[0020] According to a preferred embodiment of the present invention, in step (b), the primary urea accounts for 10-22% of the mass of the total urea-formaldehyde resin.
[0021] According to a preferred embodiment of the present invention, in step (c), the small amount of formic acid accounts for 0.02-0.08% of the total mass of the urea-formaldehyde resin.
[0022] According to a preferred disclosed example of the present invention, in step (d), the melamine accounts for 1-2% of the total mass of the urea-formaldehyde resin, the ethanolamine concentration is 20%, accounting for 0.3-0.6% of the total mass of the urea-formaldehyde resin, the secondary urea accounts for 8-16% of the total mass of the urea-formaldehyde resin, and the water accounts for 5-15% of the total mass of the urea-formaldehyde resin.
[0023] In a preferred embodiment of the present invention, in step (e), the tertiary urea accounts for 5-15% of the total urea-formaldehyde resin mass.
[0024] In a preferred disclosed example of the present invention, in step C, the glue in the coating area is melamine formaldehyde resin, and 3-5% of wear-resistant slurry, model ASM913 (produced by Shanghai Andeweiken Industrial Co., Ltd.), as well as penetrant, release agent, dust removal agent, anti-sticking agent, curing agent, etc. are added. Among them, the added amount of water is 10-20% of the resin mass, the penetrant (model F14) is 0.05-0.15% of the resin mass, the release agent (model 856A) is 0.15-0.45% of the resin mass, the dust remover (model S700) is 0.05-0.15% of the resin mass, the anti-sticking agent (model YC2002) is 0.1-0.3% of the resin mass, the plasticizer (model T58) is 0.5-1.5% of the resin mass, the photocatalyst is 0.05-0.15% of the resin mass, and the curing agent (model 1010) is 0.2-0.3% of the resin mass. All of the above additives are purchased from Shanghai Hongyi International Trade Co., Ltd.
[0025] The low-aldehyde scratch-resistant decorative panel impregnated paper prepared according to the method of the present invention has wear resistance, scratch resistance and good moisture-proof performance.
[0026] The self-made urea-formaldehyde resin of the present invention has extremely low free formaldehyde emission, and the key lies in reducing the molar ratio of formaldehyde / urea and increasing the number of times of urea addition. When the total molar ratio of the reaction is the same, the amount of urea added in batches is different, so that the pH value and the molar ratio of each reaction stage are different, which has a close relationship with the resin structure and performance. The addition of urea in batches allows the addition reaction to be carried out at a high molar ratio, which is conducive to the generation of dimethylol urea, slows down the reaction speed, makes the molecular weight distribution of the resin more reasonable, reduces the content of ether bonds in the resin, thereby reducing the formaldehyde generated by the hydrolysis of ether bonds during hot pressing bonding, thereby achieving the purpose of reducing free formaldehyde and improving the storage stability of the resin. The key to the batch addition of urea lies in the size of the molar ratio in the acid polycondensation stage. The higher the molar ratio in this stage, the more transparent the resin is and the better the stability is. The molar ratio in the acid polycondensation stage should not be less than 1.6 at the lowest and should not exceed 2.0 at the highest, otherwise it will affect the storage stability and wet bonding strength of the urea-formaldehyde resin. The higher the F / U molar ratio, the higher the content of free formaldehyde. As the molar ratio decreases, the free formaldehyde content decreases significantly. However, when the molar ratio is too low, it will affect the resin bonding strength and reduce storage stability.
[0027] Beneficial Effects
[0028] First, the present invention adopts low-formaldehyde adhesive to effectively reduce the formaldehyde content in indoor air, providing residents with a healthier and safer living environment. Secondly, the impregnated paper has excellent wear resistance and scratch resistance after special treatment, which can keep the surface smooth and tidy for a long time, reducing the wear marks caused by daily use. In addition, this impregnated paper also has good moisture resistance, and can maintain stable performance even in a humid environment, and is not easy to deform or mold. In terms of aesthetics, low-formaldehyde scratch-resistant decorative panel impregnated paper provides a variety of colors and patterns to choose from, which can meet the needs of different decoration styles and personal preferences, making the home space more colorful. At the same time, it is easy and quick to install, easy to maintain and easy to clean, which greatly reduces the maintenance cost during long-term use. In summary, low-formaldehyde scratch-resistant decorative panel impregnated paper has become an ideal choice for modern home decoration with its multiple advantages such as environmental protection, durability, beauty and easy maintenance. It not only improves the quality and comfort of home decoration, but also meets the needs of modern people for health, environmental protection, beauty and other aspects. Therefore, when choosing home decoration materials, low-formaldehyde scratch-resistant decorative panel impregnated paper is undoubtedly a high-quality option worth considering. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.
[0030] A method for manufacturing low-aldehyde scratch-resistant decorative panel impregnated paper, comprising:
[0031] 1. Preparation process of urea-formaldehyde resin for low formaldehyde impregnation:
[0032] The ultra-low molar ratio of urea-formaldehyde resin is used to reduce the impact of the formaldehyde release of the glue on the finished adhesive tape, wherein the molar ratio of the urea-formaldehyde resin for impregnation is 1.04.
[0033] (1) Add 1048 kg of formaldehyde into the reactor;
[0034] (2) Add 30% NaOH to adjust the pH value (7.5-8.5);
[0035] (3) 322 kg of urea was added for the first time;
[0036] (4) Raise the temperature to 80°C and then slowly raise the temperature to 95°C (30 minutes to complete);
[0037] (5) Keep the reaction at 95 degrees for one hour;
[0038] (6) Add formic acid to adjust the pH value to 4.6-4.8 (actually add 0.945 kg, pH value 4.63), react for about 20 minutes, and the fog point measured in 20-degree water is OK;
[0039] (7) Add 32 kg of melamine and adjust the pH value to 7.5 ± 0.2 with 20% triethanolamine solution;
[0040] (8) Keep warm for 10 minutes, add 244 kg of urea for the second time, and add 206 kg of water after keeping warm for half an hour;
[0041] (9) Cool down to 65 degrees and add 180 kg of urea for the third time;
[0042] (10) Cool down to below 40 degrees and release the glue.
[0043] The raw material ratio of the prepared urea-formaldehyde glue for impregnation is shown in Table 1:
[0044] Table 1
[0045]
[0046] 2. Impregnation process of scratch resistant impregnated film paper:
[0047] In order to solve the common problem of poor scratch resistance of the current decorative panels, a certain amount of wear-resistant slurry is added to the coating area during dipping to increase the scratch resistance. The addition ratio of the glue wear-resistant slurry in the coating area is 4%.
[0048] (11) The base paper of the film paper is impregnated once in a glue dipping tank, wherein the base paper of the film paper is 70 g of decorative paper, and the excess glue and the air in the paper are squeezed out by a glue squeezing roller, so that the mass of the resin attached to the surface of the film paper is 50±3% of the mass of the base paper;
[0049] (12) Dry in an oven at 130°C and wind speed of 1000m / s. 3 / min, speed 22m / min;
[0050] (13) applying a mixture of melamine formaldehyde resin, wear-resistant pulp and other additives in the coating area, with the upper coating amount being 50% of the mass of the base paper and the lower coating amount being 50% of the mass of the base paper;
[0051] (14) Secondary drying in oven, temperature 125℃, wind speed 900m 3 / min, speed 22m / min;
[0052] (15) Cutting, stacking and packaging.
[0053] As shown below: Table 2 is the one-time impregnation glue (IPS) formula, and Table 3 is the coating glue formula.
[0054] Table 2 One-time impregnation glue (IPS) formula
[0055]
[0056] Table 3 Coating glue formula
[0057]
[0058] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for manufacturing low-formaldehyde scratch-resistant decorative panel impregnated paper, characterized in that: The following steps are involved: A. The base paper of the film paper is pre-impregnated in a glue dipping tank. The base paper of the film paper is 50-150g of decorative paper. The excess glue and the air in the paper are squeezed out by a glue squeezing roller, so that the mass of the resin attached to the surface of the film paper is 50±3% of the base paper; B. One-time drying, temperature 115~135℃, wind speed 900~1100m 3 / min, speed 20~25m / min; C. Apply the mixed liquid in the coating area, the upper coating amount is 40~60% of the base paper mass, and the lower coating amount is 40~60% of the base paper mass; D. Secondary drying, temperature 110~140℃, wind speed 800~1000m 3 / min, speed 20~25m / min; E. Cutting, stacking and packaging; The glue in step A is an impregnation solution prepared by adding water, a penetrant and a curing agent to a homemade ultra-low molar ratio urea-formaldehyde resin, wherein water accounts for 8-12% of the mass of the urea-formaldehyde resin, the penetrant accounts for 0.3-0.5% of the mass of the urea-formaldehyde resin, and the curing agent accounts for 0.2-0.4% of the mass of the urea-formaldehyde resin; The preparation method of the self-made ultra-low molar ratio urea-formaldehyde resin comprises: (a) Add formaldehyde into the reaction kettle and stir, and adjust the pH value to 7.5-8.5 with caustic soda; (b) Add urea once and raise the temperature to 70-90°C, stop heating, and slowly raise the temperature to 95-100°C by self-heating and keep it warm for 50-70 minutes; (c) Add a small amount of formic acid to adjust the pH value to 4.6-4.8, react for 20-25 minutes, and measure the fog point in 20°C water; (d) Add melamine, adjust the pH to 7.3-7.7 with a small amount of ethanolamine solution, keep warm for 10-15 minutes, then add secondary urea, and continue to keep warm and add water for 20-40 minutes; (e) Cool down to 60-70℃, add urea three times, continue to cool down to 40℃ or below, and then produce glue.
2. The method for manufacturing the low-aldehyde scratch-resistant decorative panel impregnated paper according to claim 1, characterized in that: In step (a), the formaldehyde accounts for 40-60% of the total mass of the urea-formaldehyde resin, and the caustic soda is sodium hydroxide with a mass percentage concentration of 30-40%.
3. The method for manufacturing the low-aldehyde scratch-resistant decorative panel impregnated paper according to claim 1, characterized in that: In step (b), the primary urea accounts for 10-22% of the total urea-formaldehyde resin mass.
4. The method for manufacturing the low-aldehyde scratch-resistant decorative panel impregnated paper according to claim 1, characterized in that: In step (c), the small amount of formic acid accounts for 0.02-0.08% of the total mass of the urea-formaldehyde resin.
5. The method for manufacturing the low-formaldehyde scratch-resistant decorative panel impregnated paper according to claim 1, characterized in that: In step (d), the melamine accounts for 1-2% of the total mass of the urea-formaldehyde resin, the ethanolamine concentration is 20wt%, accounting for 0.3-0.6% of the total mass of the urea-formaldehyde resin, the secondary urea accounts for 8-16% of the total mass of the urea-formaldehyde resin, and the water accounts for 5-15% of the total mass of the urea-formaldehyde resin.
6. The method for manufacturing the low-aldehyde scratch-resistant decorative panel impregnated paper according to claim 1, characterized in that: In step (e), the tertiary urea accounts for 5-15% of the total urea-formaldehyde resin mass.
7. The method for manufacturing the low-formaldehyde scratch-resistant decorative panel impregnated paper according to claim 1, characterized in that: In step C, the mixed solution is a melamine formaldehyde resin with 3-5% wear-resistant slurry added thereto, and also includes a penetrant, a release agent, a dust remover, an anti-sticking agent, a plasticizer, a photocatalyst, and a curing agent.
8. Low-formaldehyde scratch-resistant decorative panel impregnated paper manufactured according to the method described in any one of claims 1 to 7.